Weight gain in low-birth-weight newborns and associated factors in Central Benin settings - SOSSA, JÉRÔME CHARLES; AGOSSADOU, Donelle; AZANDJEME, COLLECTE SYLVIE; METONOU, B; KEDOTE, MARIUS (My University, 2023)
Background: There is an association between low birth weight (LBW) and neonatal morbidity and mortality. The aim of the study was to identify associated factors with low 4-week weight gain among low-birth-weight newborns benefiting from the "optimized mother-newborn care model" within Bohicon health district in Benin. Methods: This was a retrospective. analytical study of 124 low-weight newborns benefiting from the "optimized mother-newborn care model". monitored for four weeks, and their mothers. Data on newborns and mothers as well as on the healthcare system were gathered through documentary review and interviews. Logistic regression was used to investigate associated factors with weight gain. Results: Of the 124 newborns monitored, more than half (S4.84%) were female, their average birth weight was 2110.24±217.0S grams, and 103 (83.06%) reached the weight threshold of2S00 grams after four weeks. The mean age of the 101 mothers surveyed was 23.47±S.23 years. High household size (OR=S.6S; CI9S%: [1.04-30.71]), absence of home visits by community health workers (OR=10.93; CI9S%: [1.S4-77.14]), breastfeeding by expressing milk directly from the breast into baby's mouth (OR=13.90: CI9S%: [2.S7-74.97]) and non-consumption of hindmilk by the newborn (OR=10.93: CI95%: [1.72-47.08]), were associated with weight gain in these low-weight newborns. Conclusions: The "optimized mother-newborn care model" appears to improve weight gain in low-birth-weight newborns. Taking into account the factors associated with low weight gain in low-weight newborns could improve the effectiveness of the implemented model in this health district